Living Arrangements as an Indicator of the Integration of Older Ethnic Russian Immigrants in Estonia - Anne Herm; Allan Puur; Michel Poulain (Demografie)
This study is about living arrangements of older ethnic Russians living in Estonia most of whom are long-term immigrants. Studies involving immigrant populations have suggested that the integration process would decrease their differences with the host population, including their living arrangement preferences. Our investigation shows that despite long-term residence in country, living arrangements’ pattern of ethnic Russians in Estonia is rather different from that of Estonians and that can be explained by low integration. The study is based on the microdata of the Estonian 2011 population and housing census and the 5% sample of the Russian 2010 census from the IPUMS database. In the first part of the analysis, we employ origin-destination perspective to comparing living arrangements of Russians in Estonia with Estonians and Russians in Russia. In the second part, we use binary logistic regression to study the association between living arrangements, migration background and integration to host society.